Improving Students’ Writing Skill by Using Modified Gist (Generating Interaction between Schemata and Text) at Fifth Semester of State Islamic College in Kerinci - Eliza Trimadona (Universitas Negeri Padang, 2014)
This paper presented the research about how modifed GIST was effective to improve students’ writing skill in semester 5 of State Islamic College in Kerinci at academic year 2009-2010. The concept of this strategy refered to text-schemata-text. Besides, this paper also described the factors which influenced the improvement of students’ writing skill by using modified GIST. By using class action research (CAR), the instruments of this research were observation sheet and test. It consisted of 3 cycles. Each cycle had better improvement, proven by the result of tests and also holistical observation and interview. Not only that, it was also found that there were some factors which influenced the improvement, they were: teaching and learning media, learning method, material, learning activity, class management, and lecturer’s approach. Finally, we may say that using modified GIST was an effective strategy toimprove students’ writing skill.